Sedimentological and carbonate isotope signatures to identify fluvial processes and catchment changes in a supposed impact ejecta‐dammed lake (Miocene, Germany). Issue 7 (20th June 2021) - Zeng, Lingqi; Ruge, Dag B.; Berger, Günther; Heck, Karin; Hölzl, Stefan; Reimer, Andreas; Jung, Dietmar; Arp, Gernot
Abstract: The identification and distinction of fluvial from lacustrine deposits and the recognition of catchment changes are crucial for the reconstruction of climate changes in terrestrial environments. The investigated drill core succession shows a general evolution from red–brown claystones to white–grey marlstones and microcrystalline limestones, which all have previously been considered as relict deposits of an impact ejecta‐dammed lake, falling within the mid‐Miocene Climate Transition. However, recent mammal biostratigraphic dating suggests a likely pre‐impact age. Indeed, no pebbles from impact ejecta have been detected; only local clasts of Mesozoic formations, in addition to rare Palaeozoic lydites from outside of the study area. Lithofacies analysis demonstrates only the absence of lacustrine criteria, except for one charophyte‐bearing mudstone. Instead, the succession is characterized by less diagnostic floodplain fines with palaeosols, palustrine limestones with root voids and intercalated thin sandstone beds. Carbonate isotope signatures of the mottled marlstones, palustrine limestones and mud‐supported conglomerates substantiate the interpretation of a fluvial setting. Low, invariant δ 18 Ocarb reflects a short water residence time and highly variable δ 13 Ccarb indicates a variable degree of pedogenesis. Carbonate 87 Sr/ 86 Sr ratios of the entire succession show a unidirectional trend from 0.7103 to 0.7112, indicating a change of the solute provenance from Triassic to Jurassic rocks, identical to the provenance trend from extraclasts. The increase in carbonate along the succession is therefore independent from climate changes but reflects a base‐level rise from the level of the siliciclastic Upper Triassic to the carbonate‐bearing Lower to Middle Jurassic bedrocks. This study demonstrates that, when information on sedimentary architecture is limited, a combination of facies criteria (i.e. presence or absence of specific sedimentary structures and diagnostic organisms), component provenance, and stable and radiogenic isotopes is required to unequivocally distinguish between lacustrine and fluvial sediments, and to disentangle regional geological effects in the catchment and climate influences.